Remarks on the Pressure Regularity Criterion of the Micropolar Fluid Equations in Multiplier Spaces - Fengjun Guo (Abstract and Applied Analysis)
This study is devoted to investigating the regularity criterion of weak solutions of the micropolar fluid equations in . The weak solution of micropolar fluid equations is proved to be smooth on when the pressure satisfies the following growth condition in the multiplier spaces , . The previous results on Lorentz spaces and Morrey spaces are obviously improved.